Pengaruh Servicescape dan Kualitas Pelayanan Frontliner Terhadap Kepuasan Nasabah (Studi Kasus Pada PT. Bank Muamalat KCU Padangsidimpuan) - Lestari, Eka; Siregar, Budi Gautama (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of Bank Muamalat KCU Padangsidimpuan which has been reviewed shows that the lack of public interest in using Bank Muamalat is due to the lack of quality of service and existing facilities, causing people to prefer conventional banks over sharia banks. The purpose of this research is to determine the influence of servicescape and frontliner service quality on customer satisfaction at PT. Bank Muamalat Indonesia KCU Padangsidimpuan. The research method used is a quantitative research method. Data collection techniques used interviews, questionnaires and documentation with a sample size of 87 respondents and used the Slovin formula technique. The data analysis technique uses statistics, namely SPSS version 23. The results of this research show that partially servicescape has a positive effect on customer satisfaction with Tcount (1.666) Ttable (1.663). The frontliner service quality variable partially has a positive effect on customer satisfaction with Tcount (4.520) Ttable (1.663). Apart from that, there is an influence of servicescape variables and frontliner service quality together (simultaneously) on PT customer satisfaction. Bank Muamalat Indonesia KCU Padangsidimpuan with Fcount (10,594) Ftable (3,105).